NIGERIAN MEDIA AND CORRUPT PRACTICES: THE NEED FOR PARADIGM SHIFT - Aderogba Adeyemi (European Scientific Journal, ESJ, 2013)
Corruption is the bane of Nigerian socio-economic development, which threatens the existence of Nigeria as a political entity. It is therefore imperative that all and sundry should engage in anti-corruption struggle. This paper examines the state of the country‟s media from the perspective of media practitioners. The survey method was employed for the study. Regardless of the efforts being made by various stakeholders in the media industry, it was discovered that the media was largely corrupt. Even though over 64 % of those sampled believed that acceptance of any form of gratifications was unethical, over 75 % of the journalists engage in corrupt practices with impunity. More than half of the 18 media outfits covered by the study are indifferent to certain indentified corrupt practices in their organizations. To curb corruption, journalism organizations should engage in sensitization programmes while conditions of service for journalists need to be considerably improved.